Kepadatan Populasi Wereng Coklat (Nilaparvata lugens, Stal.) dan Musuh Alaminya Pada Berbagai Varietas Padi di Bantul Yogyakarta - Sudarsono, Darmawan Suryo (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
A research to observe the population density of brown planthoppers (Nilaparvata lugens, Stal.) and their predator and parasitoid natural enemies has done on the rice field in Bantul regency of Yogyakarta. The research was conducted to observe the hoppers and its natural enemies on three local varieties and one superior brown planthoppers resistant variety of rice. The three local varieties of rice were Rejosari, Sri Kuning, and Sri Ayu, while the hopper resistant variety was IR 64. The observation were replicated three times. The result showed that population of brown planthoppers in the three local varieties of rice were higher than in the resistant IR 64 hybrid variety. The population of predators and parasitoid were relatively high in order to control the development of brown planthopper population. The predator Lycosa sp. and the parasitoids Anagrus sp. Â were commonly found in the ecosystem.